Comparison of pulmonary function tests in urban and rural children of Nagpur, Maharashtra, India - Jiwtode, Manoj Tukaram; Raikar, Premanand Ramkrishna (International Journal of Research in Medical Sciences, 2017)
Background: Pulmonary function tests (PFT) are considered as an essential component for evaluation of lung functions. PFTs are influenced by various parameters like anthropometric, geographic, ethnic, socio-economic parameters. Anthropological parameters are affected by nutrition and physical activities in young age, which directly affect the lung size and function. The aim of this study was to compare PFTs in urban and rural children of same district and to find out significant difference, if any. Methods: It was observational study. 150 each healthy children in the age group of 10 to 14 years were selected from urban and rural schools. After recording anthropometric data, PFTs were measured in all the children of both the groups. PFTs were compared among urban and rural children using unpaired t-test. Results: All the independent variables like age, weight and height were having linear positive correlation with PFTs (p<0.05). On comparing PFTs like Forced Expiratory Volume (FEV), Forced Expiratory Volume at the end of one second (FEV1), Percentage of Forced Expiratory Volume (FEV1%) between rural and urban children no statistically significant difference was noted (p>0.05)., but Peak Flow Expiratory Flow Rate (PEFR) was significantly more (p<0.05) in rural than urban students. Conclusions: We can conclude that during measurement of PFTs especially PEFR in children, the factor of urban and rural background must be considered in prediction equation.